Rearranging First-In First-Out (FIFO) Parts Layouts: Menata Ulang Tata Letak Bagian First-In First-Out (FIFO) - Yitno Utomo; Jumali, Muhamad Abdul; Rusdiyantoro; Alfi Rohmatil Maulidah (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
Surabaya locomotive warehouse is one part of the company PT. Kereta Api Indonesia (Persero) as a place to store spare parts for repair and maintenance purposes, especially locomotives. The implementation of these inspections and repairs, of course, requires spare parts to facilitate the maintenance process which generally spare parts are placed in storage or warehouses. The problem in the Surabaya locomotive warehouse is that the arrangement of spare parts for bin boxes for each type of group is not always fixed so that the search becomes a bit hampered. This study aims to review the repair of bin box spare parts placement on a regular basis by using the First-In First-Out (FIFO) approach to sort bin box spare parts based on their movement flow. Based on the results of the analysis, the classification of bin boxes in each type of spare parts rack group based on the flow of movement in sequence is fast moving, medium moving, and slow moving. In the fast moving spare parts bin boxes are placed on the bottom row of shelves, bin boxes that have medium moving spare parts are placed on the second and third rows of shelves. Meanwhile, bin boxes that have slow-moving spare parts will be placed on the top shelf. After classifying the spare parts in the bin box, an addressing area is made on each row of the rack to determine the location of the spare part position.